Design and analysis of a hybrid-excited coaxial magnetic gear utilising DC field excitation coils - Mohd Ab Halim, Mohd Firdaus; Tharma Raja, Sarweash Rao; Ahmad, Fauzi; Syed Othman, Syed Muhammad Naufal (Wydawnictwo SIGMA-NOT, 2025)
This paper presents a hybrid-excited coaxial magnetic gear (HE-CMG) with direct current (DC) field excitation coils (FECs). In the outer rotor, the north permanent magnets (PMs) are replaced with cylindrical iron poles, slotted to form a stator slot-like structure with defined teeth, and DC FECs are wound around the teeth. A 2D finite element analysis (FEA) shows that although torque is reduced compared to conventional CMGs, the design lowers PM usage and has the potential to match or exceed traditional torque transmission in future developments.